Oligonucleotide Array and VITEK Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry in Species Identification of Blood Yeast Isolates - Li, Ming-Chi; Chang, Tsung C.; Chen, Hung-Mo; Wu, Chi-Jung; Su, Shu-Li; Lee, Susan S.-J.; Chen, Po-Lin; Lee, Nan-Yao; Lee, Ching-Chi; Li, Chia-Wen; Syue, Ling-Shan; Ko, Wen-Chien (Frontiers in Microbiology, 2018)
We evaluated matrix-assisted laser desorption ionization time-of-flight mass spectrometry using VITEK MS (IVD database) and an oligonucleotide array based on the internal transcribed spacer-1 (ITS-1) and ITS-2 sequences of rRNA genes for the identification of Candida spp. from blood cultures. Five-hundred-twelve consecutive bloodstream yeast isolates were collected daily and initially identified by the phenotypic automated method (VITEK YBC or VITEK2 YST card). Inconsistent results were confirmed by D1-D2 region of 28S rRNA genes and ITSs. Excluding two unidentified yeast isolates, the oligonucleotide array and VITEK MS correctly identified 99.6% (508) and 96.9% (494) of 510 yeast isolates, respectively. The oligonucleotide array and VITEK MS demonstrated high correct identification rates for four major Candida species (C. albicans 100%, 98.4%; C. glabrata 100%, 100%; C. parapsilosis 100%, 93.3%; C. tropicalis 100%, 97.3%), but lower correct identification rates for other Candida species (91.7% and 87.5%, respectively). In conclusion, the identification performance of the oligonucleotide array is comparable to that of VITEK MS, and can serve as a supplemental tool for the identification of Candida species.